Identification of Chemical Compounds from Karamunting Stem (Rhodomyrtus tomentosa) by Thin Layer Chromatography - Agustinawati Umaternate (Borneo Journal of Pharmacy, 2019)
Karamunting or Kalimantan Grapes (Rhodomyrtus tomentosa) is a medicinal plant from Central Kalimantan that is easily found in shrubs. Based on hereditary experiences of the people of Central Kalimantan, karamunting can be used for the treatment of various diseases, one of which is diabetes. This study aims to identify the chemical compounds contained in the karamunting stem. The method used is thin layer chromatography with eluent n-hexane : ethyl acetate and methanol : chloroform. Besides, a color reaction was carried out to determine the group of compounds contained in the methanol extract of the karamunting stem. The TLC results show better stain separation in eluent n-hexane : ethyl acetate with the formation of four stains. Positive results are indicated by the content of phenol, saponin, flavonoid and terpenoid compounds. The existence of this group of compounds can be a clue to further research on the truth of the efficacy of karamunting.